2012
DOI: 10.1007/s12402-012-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: potential transcription markers for adult attention-deficit hyperactivity disorder in whole blood

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a common behavioural disorder that affects not only children and adolescents but also adults; however, diagnosis of adult ADHD is difficult because patients seem to have reduced externalized behaviour. ADHD is a multifactorial disorder in which many genes, all with small effects, are thought to cause the disorder in the presence of unfavourable environmental conditions. Therefore, in this pilot study, we explored the expression profile of a list of previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…SLC6A3, DRD5, TPH1, SNAP25. In a pilot study in aADHD, some authors demonstrated that combining the gene expression levels of these genes as predictors resulted in sensitivity and specificity of over 80% (Grunblatt et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…SLC6A3, DRD5, TPH1, SNAP25. In a pilot study in aADHD, some authors demonstrated that combining the gene expression levels of these genes as predictors resulted in sensitivity and specificity of over 80% (Grunblatt et al 2012).…”
Section: Methodsmentioning
confidence: 99%